Patterns of Alcohol Consumption in Brazilian Adults - De Moraes-Ferrari, G (Nature Research, 2022)
In this study, we aimed to describe the patterns of alcohol consumption in Brazilian adults by sociodemographic characteristics and states according to sex. Cross-sectional study including 87,555 adults from the 2019 Brazilian National Health Survey who responded to a questionnaire on alcohol consumption and were classified as non-drinkers (0 g/day), light (1–12.5 g/day), moderate (12.6–49.9 g/day), and heavy drinkers (≥ 50 g/day). Of the Brazilian adults, 73.5% were non-drinkers. Among the drinkers, 14.8% were light drinkers. 82.6% of heavy drinkers were men. White participants drank more than non-white participants, except black women who were 38% more likely to be moderate drinkers than white women (ROR 1.38, 95% CI 1.09 to 1.76). Unmarried were more likely to be drinkers. Women over 55 and men over 65 years old were less likely to be drinkers. Compared to participants with none or incomplete primary education, both men and women with higher educational attainment were more likely to be light and moderate drinkers. The largest consumption of alcohol was found in Sergipe and Mato Grosso for men, and Mato Grosso do Sul and Bahia for women. Our findings may be useful to inform policies for reducing alcohol consumption in Brazil. © 2022, The Author(s).